Pengaruh Lingkungan Kerja, Disiplin Kerja, dan Komitmen Organisasi Terhadap Kinerja Karyawan Pada PT. Japfa Comfeed Indonesia Tbk Hatchery Bandar Masilam - Khairul Amri Simbolon; Ferry Adriansyah; Kumala Vera Dewi (Management And Business Progress, 2026)
This study aims to determine and analyze the influence of the work environment, work discipline, and organizational commitment on employee performance at PT. Japfa Comfeed Indonesia Tbk Hatchery Bandar Masilam. The research method used is quantitative with data collection through questionnaires. The population in the study were all employees of PT. Japfa Comfeed Indonesia Tbk Hatchery Bandar Masilam. The sampling technique used was the census method where all members of the population were sampled, so the number of respondents was 50 people. The analysis method used was multiple linear regression with the help of SPSS software. The results of the study indicate that the work environment has a positive and significant effect on employee performance. Work discipline has a positive and significant effect on employee performance. Organizational commitment does not have a direct effect on employee performance. The work environment, work discipline, and organizational commitment have a simultaneous effect on employee performance.